Pengaruh Budaya Organisasi dan Disiplin Kerja terhadap Kinerja Perawat di Rumah Sakit Ibu dan Anak Buah Hati Pamulang - Hapsari, Gita; Madiistriyatno, Harries; Panjaitan, Eddy H. H (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Nurse performance is a crucial factor in providing quality healthcare services in hospitals. Organizational culture and work discipline play important roles in determining nurse performance. Rumah Sakit Ibu dan Anak Buah Hati Pamulang faces challenges in improving nurse performance, necessitating a deeper understanding of the impact of organizational culture and work discipline on performance. This study aims to analyze and evaluate the influence of organizational culture and work discipline on nurse performance at Rumah Sakit Ibu dan Anak Buah Hati Pamulang. The research employs a quantitative method with a survey approach. The sample consists of 30 nurses working at Rumah Sakit Ibu dan Anak Buah Hati Pamulang. Data were collected through a questionnaire measuring organizational culture, work discipline, and nurse performance. Data analysis was conducted using multiple linear regression techniques to identify the effect of each variable on nurse performance. The results show that both organizational culture and work discipline have a significant impact on nurse performance. Positive organizational culture and high work discipline contribute to improved nurse performance, with organizational culture having a more substantial impact. These findings highlight the importance of fostering a supportive organizational culture and enhancing work discipline to achieve optimal nurse performance.